A Methods engineering study for Richmark Foods Incorporated - Javier, Nidalin (College of Engineering, 2003)
Richmark Foods Incorporated is a relatively new company that has many areas for improvement. The group was tasked to conduct a study on one of its bihon plants with its main objectives being for the group to situate methods engineering to real-world productive systems, to provide ways of measuring as well as improving system productivity, to understand and to apply the principles and applications of work study, and lastly to provide techniques for implementing change observations. The group first documented all aspects of the productions, from raw material handling to the packaging then delivery of the final product. Through interviews, direct observations, measurements and assessments, the conducting team identified and analyzed the plant's problem areas. These problems are identified with the use of problem solving techniques such as stream diagnostic charts, Ishikawa diagrams, and flow process charts. For analysis, tools such as Value Engineering tables, Job Analysis and Evaluation forms, and flowcharts are used. The group then proceeded to provide possible solutions to problems that were found. The group conducted research on the feasibility of such alternatives. An implementation plan for the proposed alternatives was made with the utilization of Gantt charts and Potential Problem Analysis Tables. It has been found that the production area has four general problems. It provides unhealthy working conditions for its employees, it makes use of an inefficient plant layout, inefficient methods are used, and lastly, there is a lack of standard operating procedures and documentation. The group provided several alternatives for problems found in every area of the production line with the objective of affecting the root causes, which are the general problems of the production area. These alternatives were mainly, the addition of new equipment and tools to improve quality control and material handling, the design of a new, more efficient plant layout, and automating the processes that were done manually. After careful analysis of proposed alternatives, it can be concluded that a favorable solution would be to automate the entire process. Doing so would eliminate the problems of the production area and would greatly increase productivity, although returns would be seen only in the long term. The group recommends that further studies be conducted on the feasibility of such an alternative. The group also recommends that the company conduct a thorough documentation of its policies and standard systems and operating procedures and that the management provide ample operator training and proper briefing with regards to the company's policies, standard operating procedures and systems. A firm enforcement of the company policies and standard operating procedures should also be implemented.